2002
DOI: 10.1097/00006676-200211000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Locoregional Chemotherapy for Patients with Pancreatic Cancer Intra-arterial Adjuvant Chemotherapy After Pancreatectomy with Portal Vein Resection

Abstract: A pilot study of postoperative intra-arterial chemotherapy showed the reduction of liver metastasis and improvement of survival among pancreatic cancer patients with portal vein resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…A tumor requiring a portal resection is likely to cause systemic metastases through the portal vein, and postoperative chemotherapy is thought to be effective. Indeed, pancreatic cancer cells have a chemosensitivity for anti-cancer agents [23], and studies have demonstrated that postoperative therapy improves the survival of the patients with resectable pancreatic cancer [20,[24][25][26][27][28][29][30]. CONKO-001 study demonstrated that GEM improved the disease-free survival of postoperative pancreatic cancer patients [31].…”
Section: Discussionmentioning
confidence: 99%
“…A tumor requiring a portal resection is likely to cause systemic metastases through the portal vein, and postoperative chemotherapy is thought to be effective. Indeed, pancreatic cancer cells have a chemosensitivity for anti-cancer agents [23], and studies have demonstrated that postoperative therapy improves the survival of the patients with resectable pancreatic cancer [20,[24][25][26][27][28][29][30]. CONKO-001 study demonstrated that GEM improved the disease-free survival of postoperative pancreatic cancer patients [31].…”
Section: Discussionmentioning
confidence: 99%
“…Following cellular adhesion, freshly prepared anticancer drugs, including VCR, 5-FU, CDDP, were added with the final concentration being 0.01-, 0.1-, 1-and 10-times the human peak plasma concentration for each drug, as previously described (19). The peak serum concentrations of various anticancer drugs are 0.5 µg/ml for VCR, 10 µg/ml for 5-FU and 2.0 µg/ml for CDDP (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…In our institution, standard treatment for esophageal carcinoma with involved regional lymph node metastases [20,21]. In this study, we analyzed whether this strategy was effective for esophageal squamous cell carcinoma with regional lymph node metastasis (N1).…”
Section: Discussionmentioning
confidence: 99%
“…The MTT assay is a rapid and quantitative colorimetric system for determination of chemosensitivity of human tumor cells; however, use of this assay for solid tumor tissues has been limited because of contamination by nonmalignant cells in tumor specimens. We have recently circumvented contamination of nonmalignant cells by highly purified fresh human tumor cells when the MTT assay is used for chemosensitivity testing of fresh human samples [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%